A novel method for structural diagnosis based on passing vehicle response. (November 2017) - Hong, Wan; Zhang, Xiangyu; Lv, Kui; Jiang, Yuchen; Fang, Xuan; Hu, Xiamin
An output-only method for structural diagnosis based on passing vehicle response is proposed in this article. Theoretical derivation reveals that the area of displacement response from only one sensor when vehicle loads pass over a bridge is in relation to global bending stiffness. Therefore, it can be preliminarily ascertained whether damage occurs in structure by comparison of the area of displacement responses before and after damage. Then, in order to localize damage, a damage index composed of displacement responses from several sensors is presented. The damage index has corresponding relationship with local bending stiffness and it is irrelevant to vehicle load parameters. Meanwhile, the method is suitable for both dynamic moving load and static vehicular load test. Case study of a box-girder bridge and experimental data verify the accuracy of the method, and different kinds of vehicle loads at different speeds basically have no influence on the method. In addition, the comparison between the method of curvature of displacement influence line and the presented method is also made, and the results show that the presented damage index is free from the effect of vehicle speeds while the damage index of curvature of displacement influence line is susceptible to vehicle speed.